2021
DOI: 10.3390/nano11102611
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Semiconductor Nanostructured Based Holmium-Doped ZnO: Structural, Luminescent and Room Temperature Ferromagnetic Properties

Abstract: This research work describes the synthesis of ZnO nanostructures doped with Ho3+ ions using a conventional sol–gel synthesis method. The nanostructured produced exhibited a wurtzite hexagonal structure in both ZnO and ZnO:Ho3+ (0.25, 0.5, 0.75 mol%) samples. The change in morphology with addition of Ho3+ dopants was observed, which was assigned to Ostwald ripening effect occurring during the nanoparticles’ growth. The photoluminescence emission properties of the doped samples revealed that Ho3+ was emitting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Goel et al reported 5% doping of holmium in ZnO with micron-sized particles . Kabongo et al reported only a 0.75% molar ratio of holmium in ZnO . Ayon et al used the sol–gel method to synthesize holmium-doped ZnO nanorods with a maximum 5% molar ratio of holmium doping .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goel et al reported 5% doping of holmium in ZnO with micron-sized particles . Kabongo et al reported only a 0.75% molar ratio of holmium in ZnO . Ayon et al used the sol–gel method to synthesize holmium-doped ZnO nanorods with a maximum 5% molar ratio of holmium doping .…”
Section: Introductionmentioning
confidence: 99%
“…33 Kabongo et al reported only a 0.75% molar ratio of holmium in ZnO. 31 Ayon et al used the sol−gel method to synthesize holmium-doped ZnO nanorods with a maximum 5% molar ratio of holmium doping. 32 In the present study, uniform holmium-doped ZnO nanoparticles were successfully synthesized without the use of stabilizers, achieving a 7.5% molar ratio of holmium doping in ZnO.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compilation is clearly divided into three categories: (i) optoelectronics, (ii) photovoltaics and (iii) photocatalysis. In the optoelectronics section, the publication of Kabongo et al describes the synthesis of ZnO doped with Ho, exhibiting ferromagnetic properties under microwave excitation [1]. The second publication, by Rauwel et al, reports on the combination of ZnO nanoparticles with CNT and Ag nanoparticles, and emphasizes the plasmonic effect of Ag nanoparticles in the enhancement of UV emission owing to the Burstein-Moss effect [2].…”
mentioning
confidence: 99%